Experimental infection of one-day-old chicks with Salmonella Serotypes Previously isolated from poultry facilities, wild birds, and swine - Sousa, E De [UNESP]; Werther, K [UNESP]; Berchieri Junior, A [UNESP]; Almeida, Am [UNESP]; Ardisson, Fa [UNESP]; Silva, Ac [UNESP]; Candioto, Cg [UNESP]; Fernandes, Sa [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2013)
In order to maintain the high production and export rates achieved by the Brazilian poultry industry, it is necessary to prevent and control certain disease agents, such as Salmonella spp. Using bacterial cultures, the aim of the present study was to investigate the prevalence of Salmonella spp. in specimens collected from broiler facilities. Local wild birds were also sampled, as well as the feces of swine housed on the poultry farm. After sample collection, the isolated serotypes were subsequently inoculated into broiler chicks to determine their effects. Positive samples were collected from the following locations in the poultry facilities: poultry litter (S. serotype 4,5,12:R:-; S. Heidelberg; S. Infantis), broiler feces (S. Heidelberg; S. serotype 6,7:R:-; S. serotype 4,5,12:R:-; S. Tennessee), water (S. Glostrup; S. serotype 6,8:d:-;), and lesser mealworms (Alphitobius diaperinus) found in the litter (S. Tennessee). Among the 36 wild birds captured, S. Heidelberg was isolated from one bird's organs and intestinal contents (Colaptes campestris), and S. Enteritidis was isolated from another bird's intestinal contents (Zenaida auriculata). Salmonella Panama and Salmonella Typhimurium were isolated from swine feces. One-day-old chicks (150) were divided into 10 groups of 15 animals each. Each group was orally inoculated with a previously isolated serotype of Salmonella. Soft stools were observed on the cage floor and around the birds' cloaca between 3 and 12 days post-infection (dpi). The different serotypes of Salmonella used to inoculate the chicks were re-isolated from the spleen, liver, and cecal content samples of the infected birds on 15 and 21 dpi.
Keywords: Bacteriology; disease of poultry; diseases of wild birds